IDENTIFICATION OF SELF COMPASSION IN TEENAGERS AT KASIH KARUNIA PARE ORPHANAGE - Erva Elli Kristanti; Dyah Ayu Kartika W.S; Putu Indraswari (Indonesian Health Literacy Journal, 2024)
Self-compassion is one way of explaining an individual's ability to survive, understand and realize the meaning of an experience as something positive (Neff, 2003). The aim of this research is to identify Self Compassion in teenagers at the Kasih Karunia Pare Orphanage. The research method used is descriptive. The population in this study was all 25 teenagers at the Kasih Karunia Pare Orphanage. Collecting data to identify Self Compassion using the Self Compassion Scace (SCS) questionnaire was given once to respondents. The data was then analyzed using a frequency distribution table. The research results showed that 23 respondents (92%) teenagers had moderate self-compassion and 2 respondents (8%) teenagers had low self-compassion. Based on the research results, it can be concluded that most teenagers at the Kasih Karuia Pare Orphanage have a moderate level of Self Compassion. It is important to continue to give positive beliefs to teenagers at the Kasih Karunia Pare Orphanage so that teenagers have a strong identity and high integrity.